Noise Pollution and Its Impact on Health in Kathmandu Valley, Nepal: A Case Study - Puri, Puja; Awasthi, Mahesh Prasad; Chapagain, Aashish; Poudel, Samichhya; Pokhrel, Samiksha; Shrestha, Uttam Sagar; Pant, Ramesh Raj (Journal of Environment Sciences, 2025)
Noise is an unwanted and unpleasant sound that occurs in the wrong place at the wrong time. It can impair hearing, increase stress levels and reduce concentration and work efficiency. In recent years, noise pollution has been rising rapidly. This study aims to assess the extent of noise pollution and its health effects on residents of the Pepsicola area in Kathmandu Valley. A descriptive cross-sectional study design was employed, using a non-probability sampling technique. Sound pressure levels were measured during peak hours using a sound level meter (SL-4010), and data were collected through semi-structured questionnaires administered to 50 respondents across residential, commercial, industrial, traffic and school zones. The findings revealed that average noise levels were highest in industrial areas and lowest in residential zones during both morning and evening periods. Over 60% of respondents demonstrated limited awareness of noise pollution, while 70% reported experiencing significant health effects, including headaches, hypertension and emotional instability. Some of the recorded noise levels exceeded the limits set by both the World Health Organization (WHO) and the Government of Nepal (GoN), indicating a serious public health concern. To mitigate these effects, the study recommends measures such as roadside tree plantations, stricter enforcement of existing noise regulations and the implementation of effective noise reduction strategies.